2013
DOI: 10.1371/journal.pone.0056830
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK Enhances E-selectin and ICAM-1 Expression, and May Contribute to the Development of Cutaneous Vasculitis

Abstract: Our previous work indicated that TWEAK is associated with various types of cutaneous vasculitis (CV). Herein, we investigate the effects of TWEAK on vascular injury and adhesion molecule expression in CV mice. We showed that TWEAK priming in mice induced a local CV. Furthermore, TWEAK priming also increased the extravasation of FITC-BSA, myeloperoxidase activity and the expression of E-selectin and ICAM-1. Conversely, TWEAK blockade ameliorated the LPS-induced vascular damage, leukocyte infiltrates and adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…We showed that the pro‐inflammatory effects of TWEAK in vessels are associated with the induction of adhesion molecule and chemokine production. In addition, we also found that TWEAK blockade substantially reduced vascular damage and perivascular leukocyte infiltrates in lipopolysaccharide‐induced cutaneous vasculitis . In this study, both TWEAK and Fn14 expression were elevated in the dermal vessel wall of skin lesions in patients with UV, and the results suggest that TWEAK and Fn14 may contribute to the pro‐inflammatory effects on vascular EC; moreover, TWEAK‐dependent Fn14 signaling may be dominant.…”
Section: Discussionsupporting
confidence: 61%
“…We showed that the pro‐inflammatory effects of TWEAK in vessels are associated with the induction of adhesion molecule and chemokine production. In addition, we also found that TWEAK blockade substantially reduced vascular damage and perivascular leukocyte infiltrates in lipopolysaccharide‐induced cutaneous vasculitis . In this study, both TWEAK and Fn14 expression were elevated in the dermal vessel wall of skin lesions in patients with UV, and the results suggest that TWEAK and Fn14 may contribute to the pro‐inflammatory effects on vascular EC; moreover, TWEAK‐dependent Fn14 signaling may be dominant.…”
Section: Discussionsupporting
confidence: 61%
“…TWEAK induces CCL5 (RANTES) and CXCL8 (IL-8) expression in a human dermal endothelial cell line (209). TWEAK also upregulates E-selectin and ICAM-1 as shown in vitro and in an in vivo model of cutaneous vasculits (210). …”
Section: Endothelial Response To Gcs In Vasculitismentioning
confidence: 92%
“…Moreover, the TWEAK/Fn14 signals participate in the development of various dermatoses, such as psoriasis [7], atopic dermatitis [8], cutaneous vasculitis [18], human papillomavirus (HPV) infection [9], and bullous pemphigoid [10]. TWEAK/Fn14 activation also contributes to the biological processes of tumors [19].…”
Section: Introductionmentioning
confidence: 99%